Application of pancasila industrial relations to the settlement of industrial relations disputes: Field study at PT Parkland World Indonesia Pwi 2 Cikande Serang - Yus Saparudin Syah; Ujang Hibar; Enjum Jumhana (Institute Of computer Science (IOCS), 2026)
Industrial relations disputes remain a persistent challenge in Indonesia, often resulting from differences in the interpretation of workers’ rights, employers’ obligations, and the implementation of labor regulations. Although numerous studies have examined dispute resolution mechanisms from legal and procedural perspectives, limited research has explored the practical application of Pancasila values as a normative and ethical foundation for industrial relations at the enterprise level. This study aims to analyze the implementation of Pancasila principles in resolving industrial relations disputes at PT Parkland World Indonesia (PWI) 2 Cikande, Serang, and to evaluate their contribution to achieving harmonious, equitable, and sustainable labor relations. The research employed an empirical juridical approach using field research, with data collected through interviews, observations, and document analysis involving company management, workers, and labor union representatives. The findings reveal that deliberation (musyawarah), consensus (mufakat), social justice, and mutual respect constitute the primary principles guiding bipartite negotiations before formal litigation, thereby reducing conflict escalation and fostering cooperative industrial relations. The novelty of this study lies in integrating Pancasila as both a constitutional legal foundation and a practical dispute-resolution framework within a manufacturing industry setting. These findings provide theoretical enrichment for Indonesian industrial relations law and offer practical recommendations for employers, labor unions, and policymakers to institutionalize Pancasila-based dispute resolution as a strategy for promoting industrial harmony and preventing prolonged labor conflicts.